Isolation And Identification Of Antifungal Compounds Of Jeringau Leaf (Acorus calamus Linn.) As A Control Athelia rolfsii Sacc. Fungus That Causes Stem Rot Disease Of Soybean Plants - Prawanayoni, Susun Susun; Sudirga, Sang Ketut (Metamorfosa: Journal of Biological Sciences, 2020)
The study was carried out to isolate and  identify active compounds in jeringau leaf extract ( Acorus calamus ) and test their activity to inhibit the growth of Athelia rolfsii fungus that causes stem rot in soybean plants. The study began with extraction of Jeringau leaves, extract inhibition test on Athelia rolfsii fungus, partition, fractionation with column chromatography and thin layer chromatography (TLC), fraction inhibition test and identification of active compounds by Gas Chromatography-Mass Spectroscopy (GC-MS) analysis. Coarse jeringau leaf extract can inhibit A. rolfsii fungus with inhibition zone diameter of 25 mm. The results of the analysis of active fractions of jeringau extract using GC-MS (GCMS-QP2010 Ultra SHIMADZU) obtained 24 active compounds namely: Ethanol, 2-(2-ethoxyethoxy)-CAS; 6-Okthenal,3,7-dimethyl; beta-Citronellol; Trans-Geraniol; 6-Octen-1-ol 3,7-dimethil-acetate; Benzene 1-methoxy-4-(2-propenil); 2,6-Otahen-1-ol 3,7-dimethil-acetate; Caryophyllen; 3-Allyl-6- methoxyphenol; Dodecanoic acid methil ester;  Methil tetradecanoate;  Cis-Asarone; Alpha hexylcinnamic aldehyde; Hexadecanoic acid methyl esteter; 7-Acethyl-6-ethyl-1-1-4-4-tetramethylhetralin;  benzyl benzoate;  (2(Chloro-phenyl)-(2-Methoxy-6-MI; 9-Octadecenoic acid methyl ester;   9.12-Octadecadienoic acid  (Z.Z)-methyl ester; Oxinaneoctanoic acid 3-octyl-methyl ester cis:; Octadecenoic acid 9.10-didydroxyl-methyl ester; Oxinaneoctanoic acid 3-octyl-methyl trans;  9-Octadecenoic acid (Z)-methyl ester (CAS); 1.2-Benzenedicarboxylic acid, bis (2-ethylhexy).    Keywords: Extract, isolation, identification, jeringau, Athelia rolfsii